Experimental and numerical study on carbody hunting of electric locomotive induced by low wheel–rail contact conicity. Issue 2 (1st February 2021) - Sun, Jianfeng; Chi, Maoru; Jin, Xuesong; Liang, Shulin; Wang, Jian; Li, Wei
Abstract : In particular locations of the railway track, the excessively polished rail in the inner corner and the large rail cant will lead to an extremely low wheel–rail contact conicity. Consequently, the carbody hunting instability arises and deteriorates the ride comfort of passengers. In this paper, the carbody hunting instability of an electric locomotive is observed and tested. Combined with the analysis of wheel–rail contact and track condition, the ride comfort and running stability indices are evaluated. The dynamic model for the locomotive is established. The measured wheel and rail profiles as well as the curve radius and superelevation are integrated into the simulation model to reproduce the phenomenon that the carbody hunting displayed violent in the straight line while the abnormal vibration disappeared in the curve segment. The linearised and non-linear study on the optimisation of suspension parameters are carried out to solve the carbody hunting instability. Finally, the optimised measures that decreasing the series stiffness and damping of the yaw damper as well as the primary longitudinal stiffness are put forward, and verified by the on-track test. The investigation enriches the study of carbody hunting instability and gives some ideas to probably solve the abnormal vibration.